Associations of Substance Use Behaviors With Suicidal Ideation and Suicide Attempts Among US and Chinese Adolescents - Guo, Lan; Wang, Wanxin; Du, Xueying; Guo, Yangfeng; Li, Wenyan; Zhao, Meijun; Wu, Ruipeng; Lu, Ciyong (Frontiers in Psychiatry, 2021)
Background Adolescence has been described as a period of increased health risk-taking behaviors. Given the variety of cultural contexts, healthcare systems, and public health policies in different regions, the present study aimed to determine whether there are similar or different associations of substance use behaviors with suicidal ideation and suicide attempts among US and Chinese adolescents. Methods This study included a total of 14,765 US adolescents from the 2017 National Youth Risk Behavior Surveillance System (YRBSS) and 24,345 Chinese adolescents from the 2017 School-based Chinese Adolescents Health Survey (SCAHS). Results The proportions of suicidal ideation and suicide attempts were 17.4% and 5.7% among US adolescents, which were higher than those among Chinese adolescents (suicidal ideation: 13.7% and suicide attempts: 2.7%). Among Chinese adolescents, the most common substance use behavior was “ever alcohol use (55.4%)”, followed by “ever cigarette use (11.6%)”. Among US adolescents, the most popular substance was alcohol (ever used: 55.9%), followed by marijuana (ever used: 34.6%). Moreover, alcohol use was significantly related to suicidal ideation/suicide attempts only in Chinese adolescents (suicidal ideation: Adjusted odds ratio [AOR]=1.88, 95% CI=1.71~2.06; suicide attempts: AOR=2.12, 95% CI=1.71~2.63), and marijuana use was associated with suicidal ideation and suicide attempts only in US adolescent group (suicidal ideation: AOR=1.23, 95% CI=1.06~1.44; suicide attempts: AOR=1.51, 95% CI=1.21~1.87). Moreover, although the associations of prescription pain medication use with suicide attempts were significant in both Chinese and US adolescent groups, the adjusted associations were stronger in Chinese adolescents than in US adolescents (Chinese adolescents: AOR=3.97, 95% CI=2.76~5.72; US adolescents: AOR=1.76, 95% CI=1.43~2.16; P<0.05). Conclusions The associations of alcohol use with suicidal ideation and suicide attempts were only significant in Chinese adolescents. Marijuana use was associated with suicidal ideation and suicide attempts only in the US adolescent group. Although the associations of prescription pain medication use with suicide attempts were significant in both Chinese and US adolescent groups, the adjusted associations were significantly stronger for Chinese adolescents. These findings might be related to the differences in cultural contexts, healthcare systems, and public health policies in the two different countries.